Organocatalyzed living radical polymerization of itaconates and self-assemblies of rod-coil block copolymers - Hu, Keling (2020)
Organocatalyzed living radical polymerizations of itaconates are studied, yielding low-dispersity linear and star polymers (Đ = Mw /Mn = 1.28-1.46) up to Mn = 20 000 and monomer conversion = 62%, where Mn and Mw are the number- and weight-average molar masses, respectively. The block polymerization with functional methacrylates, an acrylate, and styrene yields various rod-coil block copolymers. Linear A-B diblock, linear B-A-B triblock, and 3-arm star A-B diblock copolymers generate spherical micelles (nanoparticles) and vesicles (nanocapsules), depending on the polymer structures. Itaconates can be derived from bioresources, and thus the obtained polymers may serve as green polymers. Because of the biocompatibility of polyitaconates, the assemblies may serve as biocompatible nanocarriers.